2015
DOI: 10.1002/2015jd023743
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol‐induced mechanisms for cumulus congestus growth

Abstract: Tropical convection has been observed to contain three cloud modes, the middle of which is cumulus congestus clouds. Congestus clouds act to moisten the tropical atmosphere, may be mixed‐phase, and on occasion surpass the freezing level inversion from where they may develop into deeper convection. This study investigates the impacts of enhanced aerosol concentrations on the growth of congestus clouds produced in idealized cloud‐resolving model simulations run under a state of radiative convective equilibrium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 63 publications
4
54
0
Order By: Relevance
“…In contrast, our simulations suggest that the precipitation response is mainly driven by changes in latent heating below the 0 • C level. The idealised studies of Sheffield et al (2015) and Lebo (2014) have also found changes in the warm-phase section of the clouds to dominate over latent heating changes in the mixed-phase part. The increase in warm-phase latent heating in Sheffield et al (2015) and Lebo (2014) is due to a more efficient vapour deposition on the more numerous cloud droplets in polluted conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our simulations suggest that the precipitation response is mainly driven by changes in latent heating below the 0 • C level. The idealised studies of Sheffield et al (2015) and Lebo (2014) have also found changes in the warm-phase section of the clouds to dominate over latent heating changes in the mixed-phase part. The increase in warm-phase latent heating in Sheffield et al (2015) and Lebo (2014) is due to a more efficient vapour deposition on the more numerous cloud droplets in polluted conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Freezing releases latent heat aloft and invigorates these cloud systems [47], but also in the lower levels of the cloud more latent heat is released by enhanced condensational growth [88,93]. This is partly counteracted by the reduced buoyancy due to increased water loading.…”
Section: Aerosol Effects On Deep Convective Cloudsmentioning
confidence: 99%
“…[] and Sheffield et al . [] contend that aerosols are responsible for the transition from shallow convective to congestus or deep convective modes, especially in pristine environments such as over the West Pacific Warm Pool. Storer et al .…”
Section: Introductionmentioning
confidence: 99%